PENGARUH KOMITMEN ORGANISASI, MOTIVASI, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. SARI LEMBAH SUBUR KABUPATEN PELALAWAN - Muhammad, Saputra Deni; Machasin, Machasin; Rendra, Wasnury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to find out about the effect of organizational commitment, motivation, and work discipline on the employee performance at PT. Sari Lembah Subur, Pelalawan Regency. The population and the sample in this study were all permanent employees in 2018 of 78 people. The method of data analysis used was multiple linear regression through the SPSS 23 program. Regarding with the result of qualitative research, it indicates that organizational commitment at PT. Sari Lembah Subur is still not good enough. The low dedication and dedication of employees at work and employees are also considered as less loyal toward the company. Work motivation of employees is also still relatively low toward the company. This is due to the lack of stimulus, appreciation and career opportunities. While, the work discipline of employee has been classified as good manner, however, the company is necessary to place the employees in accordance with their abilities and educational background. Further, dealing with the result of quantitative test shows that organizational commitment, motivation and work discipline simultaneously and partially effect significantly on the performance of employees at PT. Sari Lembah Subur, Pelalawan Regency. Satisfying organizational commitment, high work motivation and good work discipline will lead to the optimal employee performance.Keywords: Organizational Commitment, Motivation, Work Discipline and Employee Performance.